Beauveria bassiana (Ascomycota: Hypocreales) Introduced as an Endophyte in Corn Plants and Its Effects on Consumption, Reproductive Capacity, and Food Preference of Dichroplus maculipennis (Orthoptera: Acrididae: Melanoplinae) - Pelizza, Sebastián Alberto (2017)
In this study, the effects of strain Beauveria bassiana (LPSC 1067) as an endophyte in corn plants on consumption, fecundity, and food preference of Dichroplus maculipennis were examined. We observed that the daily consumption by grasshoppers fed with control plants was almost twice that of those that were fed treated plants. Significant differences in fecundity of grasshoppers that were fed with treated plants compared with those that only fed on control plants were also observed. The number of eggs laid per female fed with control plants was 27.2, while the number of eggs laid per female that were fed during 15 d with treated plants was 17.7. Similar results were observed when the number of embryonated eggs was evaluated. The highest number of embryonated eggs were recorded in those females that only fed on control plants (96%) while fewer embryonated eggs were recorded in grasshoppers fed for 15 d with treated plants only (25%). In relation to food preference the average consumption rate for D. maculipennis females on control corn plants was 303.8624.5mg while it was only 2562.1mg on plants treated with B. bassiana as an endophyte. In summary, we observed that B. bassiana as a corn plant endophyte negatively affected the daily consumption rate, fecundity and food preference of D. maculipennis.